The Washington Embassy
VIII, 243 p. 1 illus.
Keywords: This book is the first study of the role of British Ambassadors in shaping Anglo-American relations during the first generation of the 'special relationship'. As well as showing how ambassadors wielded influence in Washington and helped to formulate British foreign policy, it offers insights into the role of the embassy in modern diplomacy.